2019
DOI: 10.18805/ijare.a-5196
|View full text |Cite
|
Sign up to set email alerts
|

Field evaluation of biocontrol agents and biopesticides against spotted pod borer, Maruca vitrata (Geyer) on lablab

Abstract: Microplot field trial was conducted from March to May 2017 to assess the efficacy of various biopesticides, pathogen, predator and parasitoid against M. vitrata on lablab (var. Co Gb 14). The experiments were carried out in a randomized block design (RBD) with nine treatments and three replications. Results revealed that spinosad 45% SC @ 75 ml ha-1 was significantly superior to all other treatments by recording a cumulative mean population reduction of 72.58 per cent. The next in the order of efficacy were em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…Spinosad 45 SC is found to be the next best treatment which is in line with the findings of Umbarkar and parsana [6] and Lakshmi et al [7] who reported that Spinosad 45 SC was found most effective in reducing the larval population of Greengram spotted pod borer as well as increasing the yield. Emamectin benzoate 5% SG is found to be the next best treatment which is in line with the findings of Kishor et al [8] and Haripriya et al [9]. Metarhizium anisopliae is found to be the next effective treatment which is in Neem oil 5% is found to be the next effective treatment which is in line with the findings of Berani et al [11] and Srinivasan and Sridhar [12].…”
Section: Resultssupporting
confidence: 86%
“…Spinosad 45 SC is found to be the next best treatment which is in line with the findings of Umbarkar and parsana [6] and Lakshmi et al [7] who reported that Spinosad 45 SC was found most effective in reducing the larval population of Greengram spotted pod borer as well as increasing the yield. Emamectin benzoate 5% SG is found to be the next best treatment which is in line with the findings of Kishor et al [8] and Haripriya et al [9]. Metarhizium anisopliae is found to be the next effective treatment which is in Neem oil 5% is found to be the next effective treatment which is in line with the findings of Berani et al [11] and Srinivasan and Sridhar [12].…”
Section: Resultssupporting
confidence: 86%
“…Thirdly, their application may require more time and labor than that of chemical pesticides, thus increasing the cost of labor. Finally, they may not be as effective as chemical pesticides in certain cases [8]. Despite these challenges, biocontrol agents are a safe, effective, and economical method for managing plant diseases and insect pests.…”
Section: Introductionmentioning
confidence: 99%
“…Inorganic fertilizers effect on soil chemical properties was discussed by Almaz et al, (2017) and stated that the inorganic nitrogen fertilizer can be replaced with soybean residues. Haripriya et al, (2019) stated that the evaluation of biocontrol agents and biopesticides showed the need for biointensive management. Besides, pesticide residues can be found on and in the food, crops also put the animals and us at risk (Nicolopoulou, et al, 2016).…”
Section: Introductionmentioning
confidence: 99%